Factors associated with symptom severity in stress-induced exhaustion disorder: cohort characterization and cross-sectional correlations - Arthur Cully, Sean; Hatinova, Klara; van de Leur, Jakob Clason; Björnsdotter, Malin (Frontiers in Psychiatry, 2025)
IntroductionChronic stress-related conditions such as burnout and exhaustion disorder (ED) constitute a significant and growing individual and societal burden. Still, the long-term interactions between symptoms and key risk factors, including brain structure and function, remain poorly understood. To address this knowledge gap, we initiated the PROMUS project, a large-scale longitudinal brain imaging study of 350 participants on sick leave for ED in Sweden.MethodsHere, we report baseline cohort (n=300) characteristics and cross-sectional associations between symptom severity, primarily measured using the Shirom-Melamed Burnout Questionnaire (SMBQ), and demographic, occupational, psychiatric, psychological, and lifestyle factors assessed using online questionnaires.ResultsOur findings revealed significant associations between symptom severity and multiple factors, most notably depression, anxiety, sleep disturbances, quality of life, dissociation, psychological inflexibility, intolerance of uncertainty, self-efficacy, alexithymia, trauma, gratitude, educational background, emotional stability, household demands, Attention Deficit/Hyperactivity Disorder symptoms, autistic traits, perfectionism, and physical activity.DiscussionThese findings support previous research linking persistent stress conditions to a spectrum of demographic, occupational, psychiatric, psychological, and lifestyle measures. The results also add to the understanding of targetable ED symptoms and risk factors and set the direction for brain imaging analyses and longitudinal assessments in this cohort.